Creation of New Analogues of Natural Phytogormons for Increasing the Yield of Agricultural Crops - Oral, Zhylkybaev; Mereke, Alimzhanova; Kazhybek, Ashimuly; Sabina, Shoinbekova; Zulfia, Tukenova (International Journal of Engineering and Technology, 2018)
Synthesis of new potential plant growth regulators (analogues of natural phytohormones) is accomplished by mixing an equimolar mixture of aryloxypropin and 1-methylpiperidin-4-one under the conditions of Favorsky's reactions. New derivatives of acetylene aminoalcohols - the ZhOT series - have been obtained. The structure of the synthesized compounds was established by IR and NMR 1H spectroscopy. Screening of their water-soluble forms, on wheat and barley seeds, two preparations (ZhOT-4 and ZhOT-7) were selected, which exceed both the control and standards of known phytohormones, such as heteroauxin (indolyl-3-acetic acid), 6-BAP (6-benzylaminopurine) for further testing. Conducted in-depth laboratory and demonstration field tests on cereals (wheat and barley) showed high efficiency of ZhOT-4 and ZhOT-7, the indicators of which exceeded the well-known reference preparation - Agrostimulin (Ukraine). The growth regulating activity of synthesized compounds was determined. Processing of wheat seeds ZhOT-4 and ZhOT-7 increased the field germination of seeds, plant height, leaf area, the mass of the aerial part and the total area. The conducted studies showed that the biological activity of the tested compounds largely depends on the concentration and the best growth regulator is ZhOT-4. The activity of the synthesized growth regulatory compounds has been determined. Treatment of seeds of with ZhOT-4 and ZhOT-7 increased seed germination, height of plants, leave areas, weight of an elevated part and the total area, weight of an elevated part and the total area. Studies have shown that the biological activity of tested compounds is largely dependent on the concentration and the best growth regulator is ZhÐžÐ¢-4. Thus, the advanced laboratory and demonstration (small-scale) comparative tests of ZhOT-4 and ZhOT-7 and the well-known reference preparation "Agrostimulin" (Ukraine) for cereals (wheat and barley) showed high efficiency of new synthesized preparations. The use of ZhOT preparations increases the germination and germination energy, the number of spikelets, the mass of grains, the bushiness and the yield of wheat and barley, leads to the accumulation of dry mass in both the ground and underground parts of plants. The advantages of ZhOT-4 and ZhOT-7 are: high efficiency, a wide range of cultures, good solubility in water, low application dose of 0.0001% by active ingredient (1g per 1t of water) or 13-50 mg per hectare, comparable to natural phytohormones, long shelf life, safety, high yield of target products, sequential 3-stage reaction in one reactor.Â